2013
DOI: 10.4103/1658-354x.114070
|View full text |Cite
|
Sign up to set email alerts
|

The comparative evaluation of intravenous with intramuscular clonidine for suppression of hemodynamic changes in laparoscopic cholecystectomy

Abstract: Background:Clonidine diminishes stress response by reducing circulating catecholamines and hence increases perioperative circulatory stability in patients undergoing laparoscopic surgeries. The aim of this study was to compare intravenous (IV) clonidine (2 μg/kg) with intramuscular (IM) clonidine (2 μg/kg) for attenuation of stress response in laproscopic surgeries.Methods:Eighty adult patients classified as ASA physical status I or II, aged between 20 and 60 years undergoing elective cholecystectomy under gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Based on studies by others with different doses and route we aimed to use 1.5 mcg/kg of IV clonidine with fentanyl 1.5 mcg/kg as premedication for general anaesthesia to observe the effects on stress responses and found to have significant haemodynamic stability in patients who received clonidine infusion as premedication, as observed by others. [20][21][22] Due to attenuation of stress responses lesser need of use of drugs like esmolol, labetalol and nifedipine, clonidine thus also minimizes the requirement of intraoperative analgesics and inhalational agent almost by 30% which is observed on study by Sung et al 15 We also observed lesser need of nitroglycerine infusion in patients of clonidine pre-medicated group. M Laisalmi et al 23 in their study with 4.5 mcg/ kg of clonidine on neuroendocrine response and renal parameters by measuring plasma renin activity (PRA), serum anti-diuretic hormone (ADH), urine N-Acetyl-beta-D-glucosaminidase and creatinine levels and oxygen tension of the urine peri-operatively.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Based on studies by others with different doses and route we aimed to use 1.5 mcg/kg of IV clonidine with fentanyl 1.5 mcg/kg as premedication for general anaesthesia to observe the effects on stress responses and found to have significant haemodynamic stability in patients who received clonidine infusion as premedication, as observed by others. [20][21][22] Due to attenuation of stress responses lesser need of use of drugs like esmolol, labetalol and nifedipine, clonidine thus also minimizes the requirement of intraoperative analgesics and inhalational agent almost by 30% which is observed on study by Sung et al 15 We also observed lesser need of nitroglycerine infusion in patients of clonidine pre-medicated group. M Laisalmi et al 23 in their study with 4.5 mcg/ kg of clonidine on neuroendocrine response and renal parameters by measuring plasma renin activity (PRA), serum anti-diuretic hormone (ADH), urine N-Acetyl-beta-D-glucosaminidase and creatinine levels and oxygen tension of the urine peri-operatively.…”
Section: Discussionmentioning
confidence: 63%
“…Chiruvella et al 21 studied IV 1 mcg/kg of dexmedetomidine and clonidine for attenuation of stress responses during laparoscopic cholecystectomy and found dexmedetomidine more effective than clonidine however chances of hypotension and bradycardia were more with dexmedetomidine. Singh M et al 22 studied 2 mcg/kg of IV clonidine with 2 mcg/kg intramuscular clonidine injection as premedication and found better haemodynamic stability (MBP,HR) in patients receiving clonidine by IV route and more patients required treatment for hypertension who received intramuscular clonidine as premedication. Based on studies by others with different doses and route we aimed to use 1.5 mcg/kg of IV clonidine with fentanyl 1.5 mcg/kg as premedication for general anaesthesia to observe the effects on stress responses and found to have significant haemodynamic stability in patients who received clonidine infusion as premedication, as observed by others.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown effectiveness of intravenous clonidine in attenuation of hemodynamic response during laparoscopy 1,3,5 Intrathecal clonidine used as adjuvant for bupivacaine during laparoscopic cholecystectomies shown prolonged post-operative analgesia and sedation. 6 Clonidine through i.v route has been used as a single dose prior to induction or as continuous infusion throughout laparoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Increased release of vasopressin, catecholamines, or both are responsible for these hemodynamic responses [2,3,4]. Various drugs like nitroglycerine [5], beta blockers [6], opioids [7], gabapentin [8], pregabalin [9], magnesium sulphate [10], clonidine [11] and dexmedetomidine [12] are used to provide hemodynamic stability during pneumoperitoneum with variable success rate. Dexmedet-omidine inhibits the release of catecholamines and vasopressin, thus modulating the hemodynamic changes induced by pneumoperitoneum [12][13].…”
Section: Introductionmentioning
confidence: 99%